Development of Assessment Instruments For Self-Confidence, Discipline, Manners, and Responsibility in Social Studies Learning for Blended Learning in Junior High Schools - Deni Sutisna; Ruhimat, Mamat; Komalasari, Kokom; Wiyanarti, Erlina (ASANKA : Journal of Social Science and Education, 2025)
This study aims to develop an attitude assessment instrument for blended learning in junior high school social studies. The ADDIE development method was used, with qualitative and quantitative data sources. Qualitative data were obtained from interviews and observations, while quantitative data were obtained from the distribution of scores and the validity and reliability tests of the instrument. The results of the study indicate that the developed assessment instrument has gone through a series of feasibility tests, thus undergoing changes and refinements in the process until an attitude assessment instrument is ready for implementation. Ultimately, the attitude assessment instrument has met the criteria for validity and reliability. Reliability calculations also show that the developed instrument has a high level of reliability with a Cronbach's alpha value of 0.964 for attitude assessment in offline learning and 0.953 for attitude assessment in online learning. In addition, in its implementation, the attitude assessment instrument for blended learning is included in the practical category.